2021
DOI: 10.3390/en14051445
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Energy Self-Sufficient Resource Recovery Facility by Improving Energy and Economic Balance of a Municipal WWTP with Chemically Enhanced Primary Treatment

Abstract: The recent trend of turning wastewater treatment plants (WWTPs) into energy self-sufficient resource recovery facilities has led to a constant search for solutions that fit into that concept. One of them is chemically enhanced primary treatment (CEPT), which provides an opportunity to increase biogas production and to significantly reduce the amount of sludge for final disposal. Laboratory, pilot, and full-scale trials were conducted for the coagulation and sedimentation of primary sludge (PS) with iron sulpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…For example, optimizing economies of scale (pumps as large as feasible), increasing the levels of automation of key processes (aeration), or providing specialized training to operators [11,25,34]. Additionally, by implementing processes with lower energy demand, like those based on anaerobic processes for secondary treatment [7,35].…”
mentioning
confidence: 99%
“…For example, optimizing economies of scale (pumps as large as feasible), increasing the levels of automation of key processes (aeration), or providing specialized training to operators [11,25,34]. Additionally, by implementing processes with lower energy demand, like those based on anaerobic processes for secondary treatment [7,35].…”
mentioning
confidence: 99%
“…In addition, CEPT not only has an excellent organic matter capture rate, but also has advantages in organic matter retention. Budych-Gorzna et al [24] studied the coagulation and sedimentation of primary sludge by using ferric sulfate and carried it out on-site. Experiments showed that the COD removal rate reaches 70 %.…”
Section: Carbon Capture Technologymentioning
confidence: 99%
“…For example, optimizing economies of scale (pumps as large as feasible), increasing the levels of automation of key processes (aeration), or providing specialized training to operators (Avilés et al, 2019;Longo et al, 2018;Nakkasunchi et al, 2021). Additionally, by implementing processes with lower energy demand, like those based on anaerobic processes for secondary treatment (Musabandesu & Loge, 2021;Budych-Gorzna et al, 2021). ▪ Second, by the implementation of renewable energy generation technologies (Diaz-Elsayed et al, 2019;Gandiglio et al, 2017;Maktabifard et al, 2018), aiming for energy neutrality or self-sufficiency.…”
Section: Energy Options For Sustainable Wwtpsmentioning
confidence: 99%